State policy in the field of ensuring road safety in Ukraine through the prism of regulatory initiatives: analysis and prospects for implementation - S. O. Shatrava; D. Ye. Denyshchuk; O. V. Pohorilets (Law and Safety)
A comparative legal analysis of draft legal acts aimed at improving road safety (draft laws No. 8369 of 19.01.2023, No. 8353 of 12.01.2023, No. 8356 of 12.01.2023) has been carried out. It has been noted that today the legislator has carried out meaningful work aimed at improving the current legislation in terms of road safety.